2023
DOI: 10.7759/cureus.39932
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitude, Knowledge, and Practices Regarding the Usage of Antibiotics for Upper Respiratory Tract Infections in Children During the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has raised knowledge of the proper antibiotic dosage for treating childhood upper respiratory tract infections (URTIs). In order to ensure proper antibiotic usage and prevent the establishment of illnesses that is antibiotic-resistant during the COVID-19 pandemic, parental attitudes, knowledge, and behaviour surrounding antibiotic use for URTIs in children are essential. The goal of this study was to find out the parental attitude, knowledge, and practices regarding the usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A novelty of this study was its longitudinal design, as most previous studies on this subject were snapshots based on cross‐sectional surveys (Chand et al., 2023; Oikonomou et al., 2021). This longitudinal study found that parental anxiety for children remained largely stable over the course of the COVID‐19 pandemic in Victoria and Western Australia.…”
Section: Discussionmentioning
confidence: 99%
“…A novelty of this study was its longitudinal design, as most previous studies on this subject were snapshots based on cross‐sectional surveys (Chand et al., 2023; Oikonomou et al., 2021). This longitudinal study found that parental anxiety for children remained largely stable over the course of the COVID‐19 pandemic in Victoria and Western Australia.…”
Section: Discussionmentioning
confidence: 99%